2018
DOI: 10.1002/humu.23561
|View full text |Cite
|
Sign up to set email alerts
|

DMD genotype correlations from the Duchenne Registry: Endogenous exon skipping is a factor in prolonged ambulation for individuals with a defined mutation subtype

Abstract: Antisense oligonucleotide (AON)‐mediated exon skipping is an emerging therapeutic for individuals with Duchenne muscular dystrophy (DMD). Skipping of exons adjacent to common exon deletions in DMD using AONs can produce in‐frame transcripts and functional protein. Targeted skipping of DMD exons 8, 44, 45, 50, 51, 52, 53, and 55 is predicted to benefit 47% of affected individuals. We observed a correlation between mutation subgroups and age at loss of ambulation in the Duchenne Registry, a large database of phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
114
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(123 citation statements)
references
References 37 publications
1
114
0
2
Order By: Relevance
“…When looking into mutations amenable to different molecular treatments, 18 the main anticipated finding of a milder phenotype in participants with “skip 44” deletions 10–13 appeared only marginal, and only nominally significant for FVC in the meta‐analysis, possibly because of the relatively small size of these subgroups ( n = 16 in the Italian and 16 in the CINRG cohort). Even with regards to ambulatory function, it should be noted, the modifier effect of “skip 44” mutations was in fact variable 10–13 . Proposed underlying mechanisms involve alternative splicing of exon 44 by activation of cryptic splice sites at the deletion breakpoint, 31 which may vary between individuals.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…When looking into mutations amenable to different molecular treatments, 18 the main anticipated finding of a milder phenotype in participants with “skip 44” deletions 10–13 appeared only marginal, and only nominally significant for FVC in the meta‐analysis, possibly because of the relatively small size of these subgroups ( n = 16 in the Italian and 16 in the CINRG cohort). Even with regards to ambulatory function, it should be noted, the modifier effect of “skip 44” mutations was in fact variable 10–13 . Proposed underlying mechanisms involve alternative splicing of exon 44 by activation of cryptic splice sites at the deletion breakpoint, 31 which may vary between individuals.…”
Section: Discussionmentioning
confidence: 98%
“…Other than glucocorticoid (GC) treatment and standards of care, 6,8,9 several genetic factors have been called into play as modifiers of DMD severity. These include “cis‐acting” modifiers, such as specific DMD mutations which may lead to the expression of minimal, but clinically relevant quantities of dystrophin 10–13 ; and “trans‐acting” modifiers, that is, polymorphisms in genes different from DMD , that may influence the pathological consequences of dystrophin deficiency 14–17 . As specific DMD mutations are now amenable to targeted molecular treatments, 18 such as “exon skipping” antisense oligonucleotides, or small molecules promoting stop codon readthrough, delineating “natural history” trajectories in corresponding subgroups are useful.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified correlations between genotype and age at loss of ambulation in patients with DMD . Endogenous exon skipping was hypothesized to be a factor responsible for milder disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…We were unable to establish a significant correlation between mutation site, size or type and clinical milestones in our study. The anticipated relative protective effect of single exon 45 deletion [10,11] compared to other single exon mutations could not be explored in our cohort, as all three boys with single exon 45 deletions in our cohort were younger than seven years old.…”
Section: Discussionmentioning
confidence: 99%
“…A definite link between the type, site or size of a mutation on the very large DMD gene and muscle function phenotype has been difficult to establish [7,8], although a favourable clinical profile of single deletion of exon 45 compared to other single exon deletions is established [9][10][11]. A possible link has been found between the effect of the mutation on the production of central nervous system dystrophin isoforms and cognitive and neuropsychiatric difficulties [12,13].…”
Section: Introductionmentioning
confidence: 99%